2015
DOI: 10.3109/1061186x.2015.1086359
|View full text |Cite
|
Sign up to set email alerts
|

Size selectivity of intestinal mucus to diffusing particulates is dependent on surface chemistry and exposure to lipids

Abstract: Intestinal mucus provides a significant barrier to transport of orally delivered drug carriers, as well as other particulates (e.g., food, microbes). The relative significance of particle size, surface chemistry, and dosing medium to mucus barrier properties is not well characterized but important in design of delivery systems targeted to the intestinal mucosa. In this study, multiple particle tracking (MPT) was used to study diffusion of 20- to 500-nm diameter carboxylate- and polyethylene glycol- (PEG-) func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 38 publications
4
62
0
Order By: Relevance
“…Thus, SPARC protein was expected to effectively boost the accumulation of such albumin‐like nanocarrier system, here the PPy‐PEI‐P NCs, to selective target cancer cells through SPARC‐mediated cellular albumin uptake and for the subsequent specific photothermal treatment. The intestinal ECM and associated mucus layer produced by the intestinal cells is a porous structure, and those pores allow passage of particles with sizes below 500 nm even though it is negatively charged as noted in literature . In this study, the SPARC existing on the ECM produced by the intestinal cancer cell fortunately provides the niche as a target site to bind the developed carrier system for subsequent endocytosis for selective thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, SPARC protein was expected to effectively boost the accumulation of such albumin‐like nanocarrier system, here the PPy‐PEI‐P NCs, to selective target cancer cells through SPARC‐mediated cellular albumin uptake and for the subsequent specific photothermal treatment. The intestinal ECM and associated mucus layer produced by the intestinal cells is a porous structure, and those pores allow passage of particles with sizes below 500 nm even though it is negatively charged as noted in literature . In this study, the SPARC existing on the ECM produced by the intestinal cancer cell fortunately provides the niche as a target site to bind the developed carrier system for subsequent endocytosis for selective thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that this occurs by reduction of particle-mucus interactions. 40 There is also evidence that PEG-coating can decrease macrophage or HeLa uptake of iron particles where the polymer increases uptake hindrance compared with uncoated NPs. 41 Another possible explanation for the morphological alterations observed at higher doses of nanoparticles could be the presence of polyol used during the MC synthesis.…”
Section: Iron Quantification Ac Magnetic Susceptibility and Icp-oesmentioning
confidence: 99%
“…FRAP analysis demonstrated that diffusion of antibodies (IgG, IgA, and IgM) was slowed 3- to 5- fold due to low-affinity interactions within a mucus gel relative to diffusion in distilled water[48]. FRAP analysis also showed that model bile salt micelle diffusion was slowed 3-fold in mucus relative to buffer, while diffusion of molecular species that comprise bile micelles was not affected[49], indicating that bile micelles likely stay intact within the mucus barrier.…”
Section: Isolated Mucus Modelsmentioning
confidence: 99%